The Implementation Of Measures For The Prevention Of The Transmission Of COVID-19 On Behalf Of The Inmates Of Class III Correctional Facility Of Baa In 2021 - Amtiran, Ruben Jermizon; Sinaga, Masrida; Dodo, Dominirsep Ovidius (Faculty of Public Health, Nusa Cendana University, 2023)
The world has been hit by the COVID-19 virus since December 2019 which has had a direct impact on every aspect of human life, especially for Correctional Institutions considering that the risks it poses are so great for inmates because of their very concentrated population. Several actions were taken in an effort to prevent the spread of the COVID-19 virus, namely by implementing hand washing, keeping distance, using masks, spraying disinfectant, quarantine for new prisoners and limiting visits. This study aims to determine the application of COVID-19 prevention measures at Class III Baa Correctional Facility. This type of research is qualitative, namely conducting in-depth interviews with 10 informants. Data analysis uses an interactive model, namely data reduction, data presentation, and drawing conclusions. The results of the study show that hand washing has been implemented and hand washing facilities are available, advice has been given to keep distance of 1-2 meters, mandatory use of masks, spraying disinfectant throughout the prison environment, implementation of quarantine for 14 days for new prisoners and implementation of visiting services online via telephone and video calls. However the conclusion of this study is that steps to prevent the spread of COVID-19 have not been fully implemented, due to the lack of self-awareness of the inmates and the limited number of residential rooms. But, even though cases of COVID-19 are decreasing worldwide, it is hoped that inmates will continue to exhibit clean and healthy behavior, be diligent in exercising and continue to consume nutritious food as well as Class III Baa Facility, will continue to increase synergy and collaboration with related parties such as the local Health Service so that they can vaccinate prisoners in order to increase immunity against and prevent transmission of the COVID-19 virus.